A study on the theoretical predictability of extreme value distributions for natural catastrophic events - Sabolová, Radka (2014)
The thesis deals with natural disasters from the statistical point of view and treats them as extremal observations. Basics of classical extreme value theory will be summarized and new approach based on maximum entropy principle will be proposed. Both methods will be used in order to analyze real discharge data observed at the river Vltava.